Proceedings of the 29th Annual IEEE/ACM International Symposium on Microarchitecture. MICRO 29
DOI: 10.1109/micro.1996.566464
|View full text |Cite
|
Sign up to set email alerts
|

Exceeding the dataflow limit via value prediction

Abstract: Meanwhile, numerous mechanisms have been proposed and implemented to eliminate false data dependences and tolerate the latencies induced by true data dependences by allowing instructions to execute out of program order (see [8] for an overview).Surprisingly, in light of the extensive energies focused on eliminating control-flow restrictions on parallel instruction issue, less attention has been paid to eliminating data-flow restrictions on parallel issue. Recent work has focused primarily on reducing the laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
190
0
1

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(193 citation statements)
references
References 29 publications
(44 reference statements)
2
190
0
1
Order By: Relevance
“…To overcome this problem, several studies have proposed data value prediction techniques to speculatively break data dependency and improve and exploit ILP: Lipasti et al [3] introduced the basic design of value predictors in the context of superscalar architectures. Sazeides et al [4] demonstrated that different value prediction mechanisms can achieve prediction accuracies ranging from 56 to 92% and result in performance gains ranging from 7 to 23%.…”
Section: Value Predictionmentioning
confidence: 99%
“…To overcome this problem, several studies have proposed data value prediction techniques to speculatively break data dependency and improve and exploit ILP: Lipasti et al [3] introduced the basic design of value predictors in the context of superscalar architectures. Sazeides et al [4] demonstrated that different value prediction mechanisms can achieve prediction accuracies ranging from 56 to 92% and result in performance gains ranging from 7 to 23%.…”
Section: Value Predictionmentioning
confidence: 99%
“…Traditional value prediction overcomes the limits imposed by true dependencies by executing instructions with true dependencies in parallel [12,18]. This technique can also hide instructions with long execution latencies.…”
Section: Reuse Through Speculation On Tracesmentioning
confidence: 99%
“…Data value speculation has been proposed as a way of overcoming true dependences, further increasing the available parallelism [15], [33].…”
Section: A Data Value Speculation and Value Predictionmentioning
confidence: 99%